Using acoustic indices in a protected wetland: a case study from Dragoman Marsh, Bulgaria - Lukanov, Simeon; Nikolov, Boris (Ecological Questions, 2025)
Protected areas are of crucial importance for biodiversity conservation, but reliable monitoring is often associated with great costs in terms of both funding and working hours. While in recent years a number of acoustic indices have been implemented for the purpose of passive monitoring of vocally active animal species, there is still insufficient data on the effects of interactions between different taxa and the influence of anthropogenic noise. This is especially true for diverse ecosystems such as wetlands, which provide a variety of habitats for both aquatic, semi-aquatic and terrestrial animals, and are generally characterized by high species richness. The aim of this study was to establish whether three commonly used acoustic indices would be able to differentiate between vocal activity of birds and other animals, as well as traffic noise generated by passing vehicles in the protected wetland of Dragoman Marsh, Bulgaria. Using recordings from a SongMeter SM4, we registered a total of 47 bird species from 27 families, and a single frog species. We calculated three acoustic indices: ACI, ADI and AE. Although some indices (i.e., ACI) correlated with species diversity and could potentially be used to detect increase in traffic intensity, they are unlikely to differentiate between avian and anuran vocal activity.